Covidfencing, territorial development and border cities - Medeiros, E. (Congrès du centenaire de l’Union Géographique Internationale (UGI), 2022)
In the European Union, around 30% of the population live in border regions (border NUTE 3), covering approximately 40% of the territory. These regions have, for the most part, lower territorial development levels than non-border regions. The exceptions are commonly the border cities which serve as anchors of development for the entire border region, making their analysis especially important for better understanding the territorial development challenges, as well as the territorial capital and trends of border regions. In this context, this paper presents a theoretical framework of the territorial development process while linking it to the potential contribution of border cities to the territorial development of border regions. The paper concludes with the analysis of the territorial development trends of the main EU border cities during the last decade (2005-2015), largely based on statistical elements and available literature. Based on the European case, 65 border twin cities were identified and analysed. These are, with few exceptions, small and medium-sized cities, located in lagging regions. However, they hold the key to increase the territorial development potential of EU border regions, since they concentrate the human and socioeconomic capital of these regions. In addition, the analysis will debate some of the potential effects of the recent (since 2020) covidfencing process to Border cities. Indeed, the beginning of 2020 saw the global spreading of the COVID-19 pandemic, leading to a systematic closure of national borders across the world. As expected, in Europe, where close to two million commuters’ cross national borders on a daily basis to work, this new reality has provoked significant setbacks to their lives. Based on evidence already available from several sources, this paper presents some of the main impacts of the covidfencing process in the European border cities.